Relationship Between Mother's Patterns of Love and Parenting Towards Nutrition Status of Toddlers in UPTD Work Area Kalibobo Public Health Center, Nabire District - Merry Maria Mote; Nur Susan Iriyanti Ibrahim; Bau Kanang (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Background:Toddlerhood is the most central phase of a child because the growth and development of children can run quickly, precisely the age of 0-2 years is the golden period of children, because brain development reaches 80%. Cases of BB/TB nutrition at the Kalibobo Health Center UPTD, 6 cases of malnutrition, 3 cases of undernutrition, 12 cases at risk of overnutrition. The task of parents, especially mothers, in the practice of caring for toddlers so that the basic needs of nurturing patterns, loving patterns and parenting patterns affect the process of child growth and development. Objective: To determine the relationship between nurturing patterns, loving patterns and parenting patterns to the nutritional status of toddlers in the Kalibobo Health Center UPTD Work Area. Method: Quantitative research type with a cross-sectional approach. The population of 222 toddlers became 69 toddler samples using the slovin formula. The sampling technique is purposive sampling. Data analysis using Statistical Program for Social Science (SPSS) software version 16.0 with the chi-square test. Results: The test of the relationship between the sharpening pattern p-value 0.30 (>0.05), the affection pattern p-value 0.00 (<0.05), and the parenting pattern p-value 0.00 (<0.05). Conclusion: The sharpening pattern and the nutritional status of toddlers have no relationship, the affection pattern and parenting pattern have a relationship with the nutritional status of toddlers in the Working Area of ​​the Kalibobo Health Center UPTD. Suggestion: It is necessary to carry out counseling on the sharpening pattern, affection, parenting, types of activities and the importance of integrated health posts to mothers.